Pengaruh Disiplin Kerja Dan Komitmen Kerja Terhadap Prestasi Kerja Karyawan Pada PT. Payung Pusaka Mandiri Kediri - Khasanah, Uswatun; Sustiyatik, Enni; Djunaedi, Djunaedi; Utami, Sas (Politeknik Raflesia Press, 2024)
This study seeks to examine the concurrent impact of work discipline and work commitment on employee performance at PT. Umbrella Pusaka Mandiri Kediri. The research approach used is quantitative, as it involves numerical data that is examined using statistical procedures based on concrete, objective, quantifiable, rational, and systematic scientific concepts. The population under investigation consists of all employees of PT. Umbrella Pusaka Mandiri Kediri, amounting to a total of 340 individuals. A sample of 77 respondents was chosen using the Slovin technique. Data gathering methods encompass the practices of observation, recordkeeping, and questionnaires. The data analysis techniques utilized included descriptive percentage analysis, classical assumption tests, multiple linear regression analysis, simultaneous significance test (F-test), partial significance test (t-test), and the coefficient of determination (R²). The findings of this investigation can be succinctly described as follows: (1) The level of work discipline has a limited impact on the performance of employees at PT. Umbrella Pusaka Mandiri Kediri. (2) The level of dedication to work has a limited impact on the performance of employees at PT. Umbrella Pusaka Mandiri Kediri. The study found that work discipline and work dedication had a combined impact of 65% on employee performance at PT. Umbrella Pusaka Mandiri Kediri. The remaining 35% of employee performance is influenced by other factors that were not addressed in this study.